2022
DOI: 10.3389/fmicb.2022.815638
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Vesicles From Fusobacterium nucleatum Switch M0-Like Macrophages Toward the M1 Phenotype to Destroy Periodontal Tissues in Mice

Abstract: Periodontitis is a chronic inflammatory oral disease that affects nearly 50% of all adults. Fusobacterium nucleatum (F. nucleatum) is known to be involved in the formation and development of periodontitis. Outer membrane vesicles (OMVs) harboring toxic bacterial components are continuously released during F. nucleatum growth and regulate the extent of the inflammatory response by controlling the functions of immune and non-immune cells in tissues. Macrophages are important immune cells in periodontal tissue th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…First, OMVs were isolated from the liquid medium containing F. nucleatum culture by gradient centrifugation according to the previously reported protocols. , Their morphology was observed by transmission electron microscopy (TEM) (Figure A). Dynamic light scattering (DLS) data showed that the average diameter of the OMVs was 126 nm (Figure F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, OMVs were isolated from the liquid medium containing F. nucleatum culture by gradient centrifugation according to the previously reported protocols. , Their morphology was observed by transmission electron microscopy (TEM) (Figure A). Dynamic light scattering (DLS) data showed that the average diameter of the OMVs was 126 nm (Figure F).…”
Section: Resultsmentioning
confidence: 99%
“…The antigens and damage-associated molecular patterns released by dead cancer cells significantly enhanced immunogenicity. Meanwhile, noncellular OMVs containing a range of immunostimulatory components inherited from their parent cells served as a powerful and safe immune modulator. More importantly, dead F. nucleatum was transformed into a potentiator, which used released pathogen-associated molecular patterns to further facilitate the maturation of dendritic cells (DCs) and subsequent T-cell infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenic role of EVs from T. forsythia ‐infected macrophages and T. forsythia ‐derived OMVs needs to be investigated in animal periodontitis models. Recently, there have been several trials aiming to induce periodontitis and assess inflammatory responses in the periodontal tissues using silk thread ligation with OMVs derived from periodontal pathogens, including Fusobacterium nucleatum and P. gingivalis (Chen et al., 2022 ; Fan et al., 2023 ). Although we did not evaluate the inflammatory responses of EVs on the periodontal tissues, we believe that the EVs released from immune cells and periodontal pathogens of inflamed periodontal tissues may freely disseminate to systemic sites and induce inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The MVs of Burkholderia cepacia ATCC 7966TM can induce the overexpression of proinflammatory cytokines, promoting the activation and apoptosis of mononuclear lymphocytes ( 98 ). On the other hand, MVs from Fusobacterium nucleatum can polarize macrophages toward an M1-like phenotype in a murine model of periodontal disease, promoting the development of periodontitis ( 99 ). During its growth, pathogenic bacteria continuously release MVs containing toxic bacterial components, which regulate the degree of inflammatory response by controlling the functions of immune and non-immune cells in the tissue ( 100 ).…”
Section: Function Of Bacterial Mvs In Pathogenic Processmentioning
confidence: 99%